Control of selective location of homopolymer-brush grafted nanoparticles in binary polymer blends. (10th November 2020) - Zhang, Haimo; Zuo, Min; Zhu, Weipu; Zhao, An; Shi, Xuanyu; Zhang, Xinyue; Song, Yihu; Zheng, Qiang
Abstract: The location of SiO2 nanoparticles (NPs) grafted with poly(methyl methacrylate) (PMMA) brushes in a phase-separated PMMA/styrene-acrylonitrile (SAN) copolymer (60/40) blend is investigated. The NPs with brushes being much larger than the matrix PMMA chains are located in the PMMA-rich phase. Otherwise, they are easily distributed at the interfacial region between the PMMA- and SAN-rich domains, which is confirmed to be driven by the entropy-dominated interfacial energy between PMMA matrix and brush chains. Based on the semi-quantitative estimation of the interfacial energy, a diagram of state is established to precisely predict the location of NPs in the phase-separated blend matrix with respect to grafting parameters and the molecular weight of chemically similar matrix polymer, which is also applicable to data in other literatures. It can provide a simple and universal strategy to regulate the selective distribution of NPs in a wide range of nanocomposites. Graphical abstract: In order to distribute particles at the interface of A/B blends, unlike the past, which required grafting of small molecules precisely, A/B copolymers or even preparing Janus particles, we propose a method by grafting homopolymer brush A, whose length should not be much longer than that of the matrix A. It could be satisfied over a wide range without precise regulation, which is also applicable to data in other literatures. Image 1